2008
DOI: 10.1146/annurev.soc.33.040406.131740
|View full text |Cite
|
Sign up to set email alerts
|

The Sociology of Discrimination: Racial Discrimination in Employment, Housing, Credit, and Consumer Markets

Abstract: Persistent racial inequality in employment, housing, and a wide range of other social domains has renewed interest in the possible role of discrimination. And yet, unlike in the pre-civil rights era, when racial prejudice and discrimination were overt and widespread, today discrimination is less readily identifiable, posing problems for social scientific conceptualization and measurement. This article reviews the relevant literature on discrimination, with an emphasis on racial discrimination in employment, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
1,028
2
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,530 publications
(1,132 citation statements)
references
References 143 publications
(127 reference statements)
17
1,028
2
22
Order By: Relevance
“…Further research would do well to examine discrimination against candidates with a visual impairment who intend to buy as well, and could be extended to examining discrimination among credit institutions. 44 In sum, this study has shown that discrimination against individuals with a visual impairment in the rental housing market is substantial, among both private landlords and real estate agents. Given that discrimination has a negative effect on both physical and mental health 26,27,28,29 , this finding should urge health researchers to devote more attention to social causes of health problems among individuals with an impairment.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…Further research would do well to examine discrimination against candidates with a visual impairment who intend to buy as well, and could be extended to examining discrimination among credit institutions. 44 In sum, this study has shown that discrimination against individuals with a visual impairment in the rental housing market is substantial, among both private landlords and real estate agents. Given that discrimination has a negative effect on both physical and mental health 26,27,28,29 , this finding should urge health researchers to devote more attention to social causes of health problems among individuals with an impairment.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…Ethnic discrimination is usually defined as the unequal treatment of individuals or groups by virtue of their ethnic background (Midtbøen & Rogstad 2012a;Pager & Shepherd 2008). As such, for an act to be defined as discriminatory, a causal link between the ethnic background of the individual or group and the actual unequal treatment must be established.…”
Section: Ethnic Penaltiesmentioning
confidence: 99%
“…Studies of labour market discrimination employ a broad set of approaches, including studies of legal cases, qualitative research into the recruitment practices of employers and the work of employment agencies, and surveys on the subjective experiences of ethnic minorities and victims of discrimination (see reviews in Pager & Shepherd 2008;Midtbøen 2015b). However, to measure the incidence of discrimination directly, field experiments or audit studies are usually considered the 'gold standard' (OECD 2013b: 202).…”
Section: Critique Of the Ethnic Penalty Approach And The Role Of Discmentioning
confidence: 99%
“…Although, women and minorities have made important strides in the labor market over the past several decades, they still face discrimination (Tomaskovic-Devey et al 2006;Pager and Shepherd, 2008;Ridgeway 2011). For instance, they are less likely to be hired for or promoted to prestigious positions, compared to their male and white counterparts (Catalyst 1996;Reskin 2001;National Research Council 2004;Correll & Benard 2006).…”
Section: A Lay Statistician Explanation Of Minority Discrimination: Amentioning
confidence: 99%
“…Similarly, research shows high levels of sex-and race-segregation, with females and minorities disproportionately represented in sectors or occupations with lower pay (Reskin 1993;Tomaskovic-Devey et al 2006). From dominant theoretical perspectives, this persistent discrimination is somewhat surprising, given growing evidence that gender-and racial attitudes have become more egalitarian (e.g., Dovidio & Gaertner 2004;Bobo 2001;Foschi & LaPointe 2002;Pager and Shepherd, 2008), as well as the introduction of federal legislation barring discrimination based on social category membership (Burstein and Edwards 1994;Quillian 2006). But, as Reskin (2002) notes, legislation and policies aimed at barring discrimination tend to assume that discrimination is based on decision-makers' intentional or rational choices.…”
Section: A Lay Statistician Explanation Of Minority Discrimination: Amentioning
confidence: 99%